Patient-Centered Care and Uterine Fibroids - Marsh, Erica E.; Chibber, Shani; Saad, Wael (Seminars in Reproductive Medicine, 2017)
Uterine leiomyomas are the most prevalent tumors in reproductive-aged women and are a major public health concern in the United States. Commonly known as fibroids, these benign tumors continue to be the leading cause of hysterectomy and are responsible for as much as $34 million in costs annually in the United States. Despite the increasing numbers of gains that are being made in understanding the pathophysiology of these tumors, relatively little work has been done to advance understanding of care delivery with regard to these tumors, specifically the patient perspective. Herein, we provide an overview of patient-centered care, a review of the available literature on the fibroid patient's perspective, and a discussion of opportunities to re-envision patient care with regard to fibroids.
Keywords: Fibroid; patient-centered care; quality; care delivery